Evidence-based management of recurrent miscarriages - Yadava B Jeve; William Davies (Wolters Kluwer Medknow Publications, 2014)
Recurrent miscarriages are postimplantation failures in natural conception; they are also termed as habitual abortions or recurrent pregnancy losses. Recurrent pregnancy loss is disheartening to the couple and to the treating clinician. There has been a wide range of research from aetiology to management of recurrent pregnancy loss. It is one of the most debated topic among clinicians and academics. The ideal management is unanswered. This review is aimed to produce an evidence-based guidance on clinical management of recurrent miscarriage. The review is structured to be clinically relevant. We have searched electronic databases (PubMed and Embase) using different key words. We have combined the searches and arranged them with the hierarchy of evidences. We have critically appraised the evidence to produce a concise answer for clinical practice. We have graded the evidence from level I to V on which these recommendations are based.